Climate change in the south american monsoon system: present climate and CMIP5 projections - Jones, C.; Carvalho, Leila M. V. (American Meteorological Society, 2013)
The South American monsoon system (SAMS) is the most important climatic feature in South America. This study focuses on the large-scale characteristics of the SAMS: seasonal amplitudes, onset and demise dates, and durations. Changes in the SAMS are investigated with the gridded precipitation, Climate Forecast System Reanalysis (CFSR), and the fifth phase of the Coupled Model Intercomparison Project (CMIP5) simulations for two scenarios [“historical” and high-emission representative concentration pathways (rcp8.5)]. Qualitative comparisons with a previous study indicate that some CMIP5 models have significantly improved their representation of the SAMS relative to their CMIP3 versions. Some models exhibit persistent deficiencies in simulating the SAMS. CMIP5 model simulations for the historical experiment show signals of climate change in South America. While the observational data show trends, the period used is too short for final conclusions concerning climate change. Future changes in the SAMS are analyzed with six CMIP5 model simulations of the rcp8.5 high-emission scenario. Most of the simulations show significant increases in seasonal amplitudes, early onsets, late demises, and durations of the SAMS. The simulations for this scenario project a 30% increase in the amplitude from the current level by 2045–50. In addition, the rcp8.5 scenario projects an ensemble mean decrease of 14 days in the onset and 17-day increase in the demise date of the SAMS by 2045–50. The results additionally indicate lack of spatial agreement in model projections of changes in total wet-season precipitation over South America during 2070–2100. The most consistent CMIP5 projections analyzed here are the increase in the total monsoon precipitation over southern Brazil, Uruguay, and northern Argentina.